(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article is devoted to the outstanding world-famous sculptor, engaging in the philosophy of art, Ernst Neizvestny, who represents a monumental synthesis of the Russian avant-garde of Kandinsky, Malevich, Tatlin and Filonov. His works carry in itself a unique combination of the ideas of East and West and embodies the concept of synthesis of arts, the monumental style of sculpture and graphics, integrating the spiritual content and modern forms, the vision of the world as harmony and freedom – all this is symbolically expressed in the drawings, graphics, sculpture and monuments of Neizvestny. Among his works, well-known works are considered to be the monumental compositions “A Tree of Life” and “A Golden Child” in Odesa. His creative path and life are studied in the article: childhood and youth in the USSR, participation in the Great Patriotic War, fame and criticism at home, emigration to the USA (1976), and also worldwide recognition. His works compose the collections of many of the world’s leading museums such as the Museum of Modern Art in New York, the Museum of Modern Art in Paris, the Contemporary Museum in Stockholm, the Museum of Modern Art in Belgrade and the Kennedy Centre in Washington. Ernst Neizvestny is the author of essays, memoirs, was engaged in poetic creativity; read lectures at the largest universities in the world, the topics of his lectures are: “Art and Freedom”, “Art and Society”, “Dante and Dostoevskiy”. He was an honorary member of the Swedish Academy of Sciences, New York Academy of Sciences and Arts, European Academy of Arts and Sciences and Humanities. The fate and works of Ernst Neizvestny became the subject of many books, articles and films (Alexander Zinoviev’s story “Yawning Heights”, the documentary film “One Day of Truth”, based on the Nobel lecture of Alexander Solzhenitsyn).